2022
DOI: 10.1038/s41467-022-28509-z
|View full text |Cite
|
Sign up to set email alerts
|

Re-engineered BCG overexpressing cyclic di-AMP augments trained immunity and exhibits improved efficacy against bladder cancer

Abstract: In addition to its role as a TB vaccine, BCG has been shown to elicit heterologous protection against many other pathogens including viruses through a process termed trained immunity. Despite its potential as a broadly protective vaccine, little has been done to determine if BCG-mediated trained immunity levels can be optimized. Here we re-engineer BCG to express high levels of c-di-AMP, a PAMP recognized by stimulator of interferon genes (STING). We find that BCG overexpressing c-di-AMP elicits more potent si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 62 publications
4
42
0
Order By: Relevance
“…However, the results showed that the transcription levels of IFN-g, IL-2 and IL-10 in the lung were no changes after M. tuberculosis infection in the lung of all groups (Figure 2F). These data suggested that rBCG-DisA immunization induced higher level of trained immunity in the lung, and were in line with such recombinant BCG that could trigger proinflammatory cytokine responses in vitro of BMDMs and macrophage cell line (31,32).…”
Section: Rbcg-disa Elicited Greater Inflammatory Cytokines In the Lun...supporting
confidence: 66%
“…However, the results showed that the transcription levels of IFN-g, IL-2 and IL-10 in the lung were no changes after M. tuberculosis infection in the lung of all groups (Figure 2F). These data suggested that rBCG-DisA immunization induced higher level of trained immunity in the lung, and were in line with such recombinant BCG that could trigger proinflammatory cytokine responses in vitro of BMDMs and macrophage cell line (31,32).…”
Section: Rbcg-disa Elicited Greater Inflammatory Cytokines In the Lun...supporting
confidence: 66%
“…Intravesical instillation of rBCG secreting certain cytokines, such as IFN-γ [ 35 ], IFN-α [ 43 ] or IL-15 [ 57 ], or various chimeric proteins in which GM-CSF is fused to cancer antigens [ 67 , 68 , 69 ], has been shown to result in prolonged survival and enhanced tumor growth suppression compared to the installation of pBCG in various mouse models of bladder cancer. Expression of bacterial toxin fragments, such as PTA [ 93 ] or increased production of c-di-AMP [ 131 ], has also improved the performance of BCG against tumor growth in murine and models.…”
Section: Discussionmentioning
confidence: 99%
“…In another study with a different rBCG::DisA strain in which disA expression is under the control of the strong hsp60 promoter, improved protection over pBCG against M. tuberculosis challenge could be demonstrated using a guinea pig model [ 130 ]. In this strain, disA expression was increased 300-fold and c-di-AMP production 15-fold compared to the parental strain [ 131 ]. This overexpression resulted in increased induction of IRF3 and ifnb expression in infected macrophages and subsequent increased levels of TNF-α, IL-6 and IL-1ß secretion [ 130 ].…”
Section: Recombinant Bcg Strains Producing Non-protein Immunomodulato...mentioning
confidence: 99%
See 1 more Smart Citation
“…Now, c-di-AMP has been considered a key mycobacterial pathogen-associated molecular pattern (PAMP) inducing host innate immune responses, including type I IFN response and autophagy ( Woodward et al, 2010 ; Dey et al, 2015 ; Devaux et al, 2018 ; Ning et al, 2019 ; Singh et al, 2022 ). Additionally, c-di-AMP as an adjuvant enhanced antigen-induced Th1/Th2/Th17 pattern responses ( Ebensen et al, 2011 ; Ning et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%